Способи відтврення етнокультурної інформації в художньому перекладі - Приймачок, Оксана Іванівна; Pryimachok, Oksana I. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У результаті порівняльного аналізу оригінального й перекладного твору з’ясовано шляхи відтворення фонової інформації в українсько-російському художньому перекладі. Визначено коло безеквівалентних одиниць оригіналу з історико- чи етнокультурною складовою та способи передавання такої інформації (транскодування, пошук аналогів, коментування і графічне виділення).

The article is devoted to the comparative analyze of the original and translation (the material of the investigation is 6 stories by Ivan Franko and its remarkable Russian version translated by Lesia Ukrainka). The overcoming of language barrier in the translation mainly lies in the creative encoding of the words with expressive ethnocultural coloring. Therefore, the original components, that have no equivalents in any translation, are a justifiable and natural phenomenon. The following formations, which cannot be translated, have been researched words-realities (historical, everyday) and common names. It is shown, that the major ways of reproduction of specific Ukrainian components in this Russian translation are transcription and transliteration, constructions after foreign patterns (analogy), comment (paginal or inside the text) and quotes or brackets emphasis.
Reproduction means of ethnocultural information in the literary translation
Keywords: перекладознавство; слов’янські мови; художній переклад; етнокультурна інформація; безеквівалентні одиниці; theory of translation; Slavonic languages; literary translation; ethnocultural information; an unequivalent units